The Role of Pai Teachers in Overcoming Students' Difficulties in Qur'an Literacy - Faelasup, Faelasup; Nurwati (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in overcoming students' difficulties in Al-Qur'an literacy at the junior high school level. PAI teachers act as motivators, counselors, observers, facilitators, informants, and evaluators who actively support the learning process. Through regular guidance, the application of appropriate learning methods such as the Nderes method, and a personal and empathetic approach, teachers are able to help students overcome challenges in reading and writing the Al-Qur'an. Supporting factors such as a supportive curriculum, availability of learning media, teacher motivation, and family support strengthen the effectiveness of learning, while inhibiting factors such as lack of reading habits, low student awareness, and minimal family support pose challenges that need to be addressed. The positive impact of the PAI teachers' role is evident in the improved Al-Qur'an literacy skills of students, increased enthusiasm and self-confidence, as well as the strengthening of students' character and spirituality. In conclusion, the holistic role of PAI teachers, in synergy with various stakeholders, is crucial to the success of Al-Qur'an literacy learning and the formation of a faithful and morally upright generation.